Phase field modeling microstructural evolution of Fe-Cr-Al systems at thermal treatment - Wu, Lu; Qin, Jiantao; Kharchenko, Vasyl O.; Kharchenko, Dmitrii O.; Lysenko, Oleg B. (Frontiers in Energy Research, 2023)
A phase field model to study dynamics of microstructure transformations and the evolution of defect structure during heat treatment of Fe-Cr-Al systems is developed. Statistical and kinetic properties of evolving microstructure and defect structure in alloys with different content of alloying elements and at different temperatures were studied. Point defects rearrangement during precipitation is discussed in details. Universality of statistical distributions over precipitate size is revealed for considered class of alloys.